Predicting treatment outcomes of the empowerment group intervention for refugees with affective disorders: findings from the MEHIRA project - Strupf, Michael; Wiechers, Maren; Bajbouj, Malek; Böge, Kerem; Karnouk, Carine; Goerigk, Stephan; Kamp-Becker, Inge; Banaschewski, Tobias; Rapp, Michael; Hasan, Alkomiet; Falkai, Peter; Jobst-Heel, Andrea; et al. (Journal of affective disorders, 2023)
Background - Research on outcome predictors in the field of transcultural treatment for refugees and asylum seekers (RAS) is scarce. We aimed to evaluate predictors of outcome of a group intervention (Empowerment) for RAS with affective disorders which was incorporated at level three of the stratified stepped-care model within the Mental Health in Refugees and Asylum Seekers (MEHIRA) project. - Methods - A predictor analysis was performed at level three of the MEHIRA project, where 149 refugees with moderate depressive symptoms were treated either with Empowerment or Treatment-as-usual (TAU). Outcome measures were depression severity as assessed by patient-rated Patient Health Questionnaire 9 (PHQ-9) and clinician-rated Montgomery Asberg Depression Rating Scale (MADRS). Regression models with change scores (T1-T0) of PHQ-9 and MADRS as dependent variables were fit. Predictor selection was a mixed-method approach combining testing of literature-based hypotheses and explorative hypothesis-generating analyses of multiple baseline variables. - Results - Intention-to-treat (ITT) analyses revealed significant linear relationships between change in PHQ-9 and baseline depression severity (β = −0.35, t = −3.27, p = .002) and perceived self-efficacy (β = −0.24, t = −2.26, p = .027) in the treatment (verum) condition. MADRS change scores were predicted by baseline depression severity (β = −0.71, t = −8.65, p < .001) in the treatment (verum) condition. - Limitations - Due to small cell numbers, single predictors could not be evaluated reliably. - Conclusions - Severity of depression and self-efficacy at baseline were predictors of symptom improvement at level three (Empowerment) of the MEHIRA project. Comorbidity and trauma indicators did not predict outcomes in the treatment (verum) condition, pointing towards broad applicability of the Empowerment intervention in refugee populations.
Online verfügbar 23 November 2022, Artikelversion 1 Dezember 2022
Gesehen am 31.01.2023